PENGARUH KOMUNIKASI PERSUASIF SALES KARTU KREDIT TERHADAP KEPUTUSAN MENGGUNAKAN KARTU KREDIT BANK BCA - Natalia, Desy; Mawarti, Bertha Reni Pudji (STIKS Tarakanita, 2017)
Abstract: This research is motivated by the reluctance of people at a shopping center in response to the information provided credit card sales in marketing their products. This study aims to determine how much influence the persuasive communication BCA Bank credit card sales to the decision to use a credit card. The theory used is persuasive communication theory rhetoric and theory decision. The method used is simple linear regression analysis. The sample in this study was 100 respondents. The results of this study indicate that persuasive communication has a positive influence on the decision to use a credit card BCA.